Bladder pain induced by prolonged peripheral alpha 1A adrenoceptor stimulation involves the enhancement of transient receptor potential vanilloid 1 activity and an increase of urothelial adenosine triphosphate release. (20th July 2016) - Matos, R.; Cordeiro, J. M.; Coelho, A.; Ferreira, S.; Silva, C.; Igawa, Y.; Cruz, F.; Charrua, A.
Abstract: Aim: Pathophysiological mechanisms of chronic visceral pain (CVP) are unknown. This study explores the association between the sympathetic system and bladder nociceptors activity by testing the effect of a prolonged adrenergic stimulation on transient receptor potential vanilloid 1 (TRPV1) activity and on urothelial adenosine triphosphate (ATP) release. Methods: Female Wistar rats received saline, phenylephrine (PHE), PHE + silodosin, PHE + naftopidil or PHE + prazosin. TRPV1 knockout and wild‐type mice received saline or PHE. Visceral pain behaviour tests were performed before and after treatment. Cystometry was performed, during saline and capsaicin infusion. Fos immunoreactivity was assessed in L6 spinal cord segment. Human urothelial ATP release induced by mechanical and thermal stimulation was evaluated. Results: Subcutaneous, but not intrathecal, PHE administration induced pain, which was reversed by silodosin, a selective alpha 1A adrenoceptor antagonist, but not by naftopidil, a relatively selective antagonist for alpha 1D adrenoceptor. Silodosin also reversed PHE‐induced bladder hyperactivity and L6 spinal cord Fos expression. Thus, in subsequent experiments, only silodosin was used. Wild‐type, but not TRPV1 knockout, mice exhibited phenylephrine‐induced pain. Capsaicin induced a greater increase in voiding contractions in PHE‐treated rats than in control animals, and silodosin reversed this effect. When treated with PHE, ATP release from human urothelial cells was enhanced either by mechanical stimulation or by lowering the thermal threshold of urothelial TRPV1, which becomes abnormally responsive at body temperature. Conclusion: This study suggests that the activation of peripheral alpha 1A adrenoceptors induces CVP, probably through its interaction with TRPV1 and ATP release.